PENGARUH COATING ALGINATE-CHITOSAN TERHADAP PERTUMBUHAN MIKROBA PADA BUAH MELON KUPASAN - Heru Cahyana; Marcelinus Christwardana; Nur Rokhati (Jurusan Teknik Kimia, Fakultas Teknik, Universitas Diponegoro,, 2012)
Lack of peeling fruit processing now cause the rapid spoilage the fruit. Therefore, most of the industry slows microbial growth by using a coating on the fruit. In this study making edible films made from alginate and chitosan. Edible film also applied to peeling melon and tested the microbial growth during 3 days. The result showed melon which coating with chitosan film is very good because this film can hold up during 2 days with growth of microbe to 21,6 x 105 CFU/gr.